Effect of additives on the properties of magnesium oxysulfate cement - Li, Zhen-Guo; Ji, Ze-Sheng; Jiang, Li-Li; Yu, Si-Wen (Journal of intelligent & fuzzy systems, 2017)
In this paper, in order to determine effects of citric acid and phosphoric acid on properties of magnesium oxysulfate (MOS) cement, different amount of the two additives were added to MOS specimens with constant molar ratio of MgO: MgSO4: H2O. And the strength development, phase composition and microstructure were tested. The results show that 0.1wt% citric acid and phosphoric acid added into the cement will be increasing the strength and get ideal microstructure. However, for the same amount of citric acid and phosphoric acid, compressive strength of the MOS paste are higher modified by citric acid than phosphoric acid. The results from XRD indicate that the specimens modified by citric acid and phosphoric acid yield the same hydration products in MOS. As compared to the mixture with phosphoric acid, the microstructure of the mixture with citric acid is more homogenous, and with interlaced needle shaped crystals.